The effect of (negative) emotion on pro-environmental behavior : an application of the theory of planned behavior - Gibson, Ben (2016)
With climate change becoming ever-present as a huge environmental issue for the modern era to address, pro-environmental behavior (PEB) is becoming an increasingly relevant area. There seems to be a divergence between how different actors try and encourage PEB when using emotion as the motivational tool. Therefore, the current study aimed to explore this effect of (negative) emotion on decision making. The Theory of Planned Behavior (TPB) was used as the theoretical framework, with the primary research aim testing whether emotion affects the theory, and if this is a direct effect on intentions. Within the existing research, environmental values are also found to be potentially linked with the TPB variables, and as such the secondary research aim was based around this, determining if emotion has an indirect effect through values. The analysis found that the TPB holds for the control and sadness group in this setting, even with emotion as a 4th predictor. However, invoked fear adversely impacted intentions and subsequently the theory. Im-plications for this are discussed, with sadness being suggested as a more rational emotion than fear. For the secondary research aim the analysis found no link between values and the TPB, but the effect of emotion on values provided additional contradictory insight to existing value theories. Invoked fear was found to adversely affect biospheric values, leading to a discussion around coping mechanisms. Future areas of research were highlighted, specifically based on individual emotions and values.